Distribution patterns and resource assessment of Li, Ga, Ge and U from coal-fired power plants: A case study of Guizhou Province, Southwest China - Kao Tian; Qingfeng Wang; Tianrong He; Zhonggen Li (Journal of Geochemical Exploration, 2026)

Identification of the Nicotianamine synthase (NAS) gene family in wheat (Triticum aestivum L.) and the role of its member TaNAS4-A in Zn and Fe transport - Gang Liu; Yixuan Sun; Pengyuan He; Yibo Wang; Yixuan Zhang; Qingfeng Li; Fenglou Liu; Shuangxi Zhang; Yingxia Zhang; Caixia Liu; Zhangjun Wang (Functional & Integrative Genomics, 2026)

New U-series and coupled ESR/U-series dating of Hulu Cave, a key Homo erectus site in China - Qingfeng Shao; Christophe Falguères; Yunping Huang; Salah Abdessadok; Wenbo Bao; Jianing He; Xi Chen; Xianglin Zhou; Xinrui Jin; Guilan Hu; Bassam Ghaleb; Yingfei Zhang; et al. (Quaternary Science Reviews, 2026)

Ecosystem collapses in Southwest China revealed by stalagmite records during the Mid-to-Late Holocene - Shaohua Yang; Chuntong He; Shitao Chen; Qingfeng Shao; Ye Zhu; Lei Lu; Hongwei Yin; Yijia Liang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Variations in soil nutrients and functional microbe abundances govern GHGs emissions under different rice rotation regimes - Zheng Zhao; Xiangyang Gui; Jinxi He; Zhimin Sha; Qingfeng Wang; Deping Zhou; Changbin Chu; Shuhang Wu (Agricultural Systems, 2026)

Study on the effects of ultraviolet inactivation in the process of gynogenetic development of grass carp eggs induced by mirror carp sperm - Wangchao He; Yu Sun; Kuo Chen; Junwen Liang; Binchao Liang; Xinyan Zhu; Qingfeng Liu; Yang Chen; Jialin Tang; Fuzhong Yang; Chun Zhang; Bo Chen; et al. (Aquaculture, 2026)

Seasonal characteristics of atmospheric oxidizing capacity at environmental background area in North China from long-term field observations of O3, HONO and HCHO - Shuangshuang Ge; Zhiqiang Ma; Hailiang Zhang; Hanyu Zhang; Weiwei Pu; Yulu Qiu; Jinlong Hou; Chao Liu; Yucong Guo; Fan Dong; Di He; Liyan Zhou; et al. (Atmospheric Environment, 2026)

The Role and Potential Mechanism of Pectin and Pectin Oligosaccharides in Treating Intestinal Inflammation by Regulating Gut Microbiota - Qingfeng Zhang; Xiaoyu Wu; Jingyi Wang; Jiahao Miao; Cunyin Li; Shangyong Li; Ningning He; Jingyi Song (Probiotics and Antimicrobial Proteins, 2026)

An Adaptive Impedance Control Method for Underwater Dexterous Hands Based on Reinforcement Learning - Yuze Sun; Qingfeng Yao; Qiyan Tian; Naizhi He (Journal of Marine Science and Engineering, 2026)
With the continuous advancement of marine development, underwater operational tasks are becoming increasingly diverse and complex. Addressing the limitations of traditional methods and intelligent planning—which focus solely on acquiring task skills while separating grasp planning from force planning—this paper proposes a modeling approach integrating impedance control with deep reinforcement learning. Using a five-finger humanoid underwater dexterous hand as the grasping execution platform, this method achieves collaborative decision-making between grasp planning and force control for underwater dexterous hands. First, a modular underwater dexterous grasping scenario is established. Its kinematic model and inverse solution are analyzed, and the grasping problem is modeled as a Markov decision process. Second, based on the dexterous fingertip impedance control model for simulation, a grasping strategy learning method grounded in deep reinforcement learning is constructed to address the complex control challenges posed by the high degrees of freedom of the dexterous manipulator. Finally, the Proximal Policy Optimization (PPO) algorithm is employed for grasping strategy learning. An underwater dexterous grasping parallel training and testing environment is established using the Isaac Lab simulation platform to rapidly validate the learning method. Simulation results demonstrate the proposed method’s excellent dexterous compliant control performance and strong robustness to underwater variable environments: the PPO-based impedance control scheme reduces contact force variance by 56% compared to pure position control. The average maximum contact force is suppressed to 3.26 N, representing a 60.4% reduction compared to pure position control. This study achieves the organic integration of underwater hydrodynamic compensation, adaptive impedance control, and grasping strategy learning, providing a novel and effective solution for compliant grasping control of underwater dexterous manipulators.

Asynchronous abrupt changes of lake ecosystems in the Anthropocene - Dinggui Wu; Tian Xia; Qingfeng Zhao; Yibin Sun; Na Song; Man Li; Tianchen He (Global and Planetary Change, 2026)

Polyethylene microplastics specifically drive the dissemination of ARGs: Mechanisms involving microbial community restructuring and horizontal gene transfer - Xionghao Hu; Kehong Yu; Beibei Chai; Qingfeng Tang; Xia Gao; Jiamin Wang; Zhaoyang Yan; Yang Li; Lei Zhang; Chao Wang; Xiaohui Lei; Bin Chen; et al. (Science of The Total Environment, 2026)

Translational Approaches for Human Pharmacokinetics and Pharmacodynamics Prediction of Antibody-drug Conjugates: Bridging Complexity from Bench to Bedside - Wenhang Xu; Chaohsuan Pan; Qingfeng He; Xiao Zhu; Xiaoqiang Xiang (Current Pharmacology Reports, 2026)

Cost-minimizing alternative dosage regimens of imipenem/cilastatin/relebactam for patients with renal impairment: a pharmacokinetic/pharmacodynamic simulation study - Xiaoping Shi; Donghui Lao; Qing Xu; Xiaoyu Li; Bijue Liu; Qingfeng He; Xiao Zhu; Qianzhou Lv (European Journal of Clinical Pharmacology, 2026)

The 9.2 ka event during the early Holocene recorded by a stalagmite from Dongge Cave - Chuntong He; Bin Zhao; Yongjin Wang; Kan Zhao; Shaohua Yang; Qingfeng Shao; Hai Cheng; Yijia Liang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Efficient removal of Pb2+ by iron-doped hydroxyapatite: Synthesis, adsorption, kinetics and mechanisms - Yan Li; Yuxia Zhong; Hang Lei; Qingfeng He; Fengchu Liao; Sisi Tang; Mengdi Liu; Yue-Fei Zhang (Environmental Research, 2025)

Hydroclimate changes in southwestern China from Dark Age Cold Period to Medieval Climate Anomaly and their global teleconnections - Bin Zhao; Kan Zhao; Yaoqi He; Yongjin Wang; Qingfeng Shao; Hai Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Corrigendum to “Rat-to-human PBPK model of U-47700: Unveiling pharmacokinetic risks of a synthetic opioid through interspecies extrapolation” [Toxicology and Applied Pharmacology, 499 (2025) 117352] - Lina Zhong; Longjie Li; Qingfeng He; Xiao Zhu; Ping Xiang; Xiaoqiang Xiang; Hui Yan (Toxicology and Applied Pharmacology, 2025)

Using total Kalman filter to extract time-varying signals in PWV time series - Dantong Zhu; Kefei Zhang; Peng Sun; Suqin Wu; Qingfeng Hu; Peipei He; Weibo Yin; Yafei Wang; Junguo Liu (Advances in Space Research, 2025)

Correction: Establishing Clinically Relevant Specifications for Carbamazepine Tablets Using Physiologically Based Pharmacokinetic Modeling - Xiaofeng Wang; Longjie Li; Hongyi Yang; Qingfeng He; Xiao Zhu; Jiajing Wang; Bo Sun; Peng Liu; Xiaoqiang Xiang (The AAPS Journal, 2025)

Rat-to-human PBPK model of U-47700: Unveiling pharmacokinetic risks of a synthetic opioid through interspecies extrapolation - Lina Zhong; Longjie Li; Qingfeng He; Xiao Zhu; Ping Xiang; Xiaoqiang Xiang; Hui Yan (Toxicology and Applied Pharmacology, 2025)

Optimizing landslide susceptibility mapping using integrated forest by penalizing attributes model with ensemble algorithms - Wei Chen; Chao Wang; Xia Zhao; Li Bai; Qingfeng He; Xi Chen; Qifei Zhao; Ruixin Zhao; Tao Li; Paraskevas Tsangaratos; Ioanna Ilia (Earth Science Informatics, 2025)

Establishing Clinically Relevant Specifications for Carbamazepine Tablets Using Physiologically Based Pharmacokinetic Modeling - Xiaofeng Wang; Longjie Li; Hongyi Yang; Qingfeng He; Xiao Zhu; Jiajing Wang; Bo Sun; Peng Liu; Xiaoqiang Xiang (The AAPS Journal, 2025)

An Ocular Exposure Prediction for Topical Atropine in Human Using Physiologically Based Pharmacokinetic Modeling - Aole Zheng; Tian Han; Fengjiao Bu; Qingfeng He; Jianmin Shang; Paul Chi Lui Ho; Xiaoqiang Xiang; Xingtao Zhou; Taomin Huang (The AAPS Journal, 2025)

The impact of sub-pixel scale urban function on urban heat island: Insights derived from its decomposition - Qingfeng Guan; Yajun Li; Wenjia Huang; Wei Cao; Zhewei Liang; Jie He; Xun Liang (Applied Geography, 2025)

Experimental Study on the Differences in Acoustic Emission Precursor Between Rockburst and Brittle Failure Based on the Data Mining Method - Jie Sun; Dongqiao Liu; Manchao He; Qingfeng Sun; Huili Huang (Rock Mechanics and Rock Engineering, 2025)

Isolation, characterization of Bacillus subtilis and Bacillus amyloliquefaciens and validation of the potential probiotic efficacy on growth, immunity, and gut microbiota in hybrid sturgeon (Acipenser baerii ♀ × Acipenser schrenckii ♂) - Qingfeng Su; Xiaoqian Peng; Zihui Zhang; Zhongcheng Xiong; Bowu He; Pengfei Chu; Chengke Zhu (Fish & Shellfish Immunology, 2025)

Constructing local structure heterogeneity in AgNbO3-based antiferroelectrics: Achieving excellent anti-fatigue and energy storage properties - Shuaibing Gao; Zhihang Xu; Haolin Zeng; Meng Shen; Ye Zhu; Haitao Huang; Yongming Hu; Yunbin He; Qingfeng Zhang (Chemical Engineering Journal, 2024)

Comparison of drug-induced liver injury risk between propylthiouracil and methimazole: A quantitative systems toxicology approach - Qingfeng He; Min Li; Peiying Ji; Aole Zheng; Li Yao; Xiao Zhu; Jae-Gook Shin; Volker M. Lauschke; Bing Han; Xiaoqiang Xiang (Toxicology and Applied Pharmacology, 2024)

Biosynthesis pathway of flavor compound 3-methylbutanal derived from leucine by Lactococcus lactis 517: From a transcriptomics perspective - Lei Chen; Rui Liu; Chenxiang He; Mangang Wu; Qingfeng Ge; Hai Yu (Food Bioscience, 2024)

Microplastics increase the microbial functional potential of greenhouse gas emissions and water pollution in a freshwater lake: A metagenomic study - Tianyu Zhuo; Kehong Yu; Beibei Chai; Qingfeng Tang; Xia Gao; Jiamin Wang; Lixin He; Xiaohui Lei; Yang Li; Yuan Meng; Lifeng Wu; Bin Chen (Environmental Research, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Multiple Matching Attenuation Based on Curvelet Domain Extended Filtering - Qingfeng Hua; Zhang Chen; Huili He; Jun Tan; Haifeng Chen; Guanbao Li; Peng Song; Bo Zhao; Xiuping Jiang (Journal of Ocean University of China, 2024)

Modeling the Subpixel Land-Use Dynamics and Its Influence on Urban Heat Islands: Impacts of Factors and Scale, and Population Exposure Risk - Xun Liang; Song Guo; Chunyang Huang; Bingyu Wang; Yao Xiao; Jie He; Yang Li; Mengmeng Wang; Qingfeng Guan (Sustainable Cities and Society, 2024)

Global daily mask use estimation in the pandemic and its post environmental health risks: Analysis based on a validated dynamic mathematical model - Ying Zhang; Fei Jiang; Fengmin Li; Shaoyong Lu; Zihao Liu; Yuwen Wang; Yiming Chi; Chenchen Jiang; Ling Zhang; Qingfeng Chen; Zhipeng He; Xiaoli Zhao; et al. (Journal of Hazardous Materials, 2024)

Extracellular vesicles in plant-microbe interactions: Recent advances and future directions - Junsong Zhang; Liying Pan; Wenjie Xu; Hongchao Yang; Fuge He; Jianfeng Ma; Linlin Bai; Qingchen Zhang; Qingfeng Zhou; Hang Gao (Plant Science, 2024)

Application of data-driven mixing parameterization scheme in a regional ocean model - Qingfeng Feng; Guoqing Han; Yu Liu; Xiayan Lin; Bo Li; Xiaoqian Gao; Changming Dong; Yinghui He; Haili Wang (Ocean Modelling, 2024)

Quantification of allochthonous and autochthonous organic carbon in large and shallow Lake Wuliangsu based on distribution patterns and δ13C signatures of n-alkanes - Qingfeng Zhao; Aifeng Zhou; Yuxin He (Organic Geochemistry, 2024)

Sources and implications of hydroxylated isoprenoid GDGTs on the northwest shelf of Australia through the Pliocene-Pleistocene era - Yuxin He; Qingfeng Zhao; Huanye Wang (Chemical Geology, 2024)

Combined exposure of beta-cypermethrin and emamectin benzoate interferes with the HPO axis through oxidative stress, causing an imbalance of hormone homeostasis in female rats - Yuxin Li; Xianzhi He; Bin Sun; Nannan Hu; Jiamin Li; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Reproductive Toxicology, 2024)

Graphene aerogel-doped CoFe2O4/MoS2 sheets for magnetic oil absorption and the degradation of contaminants - Xin Xiang; Wenxuan Deng; Zhiyi He; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Journal of Environmental Chemical Engineering, 2023)

Enhanced VOCs adsorption and oxidation by hydrophobic-layer-modified YMn2O5 mullite catalyst with ultralow single-atom Pt loading - Jiaqin He; Yaru Wang; Xunxun Li; Jun Xiao; Yunchong Liu; Hua Li; Najun Li; Qingfeng Xu; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2023)

Zinc/carbon nanomaterials inhibit antibiotic resistance genes by affecting quorum sensing and microbial community in cattle manure production - Lizhi Li; Weikun Guan; Yihao Fan; Qin He; Dongsheng Guo; An Yuan; Qingfeng Xing; Yang Wang; Ziqin Ma; Jian Ni; Jia Chen; Qilong Zhou; et al. (Bioresource Technology, 2023)

Hydrostatic pressure drives microbe-mediated biodegradation of microplastics in surface sediments of deep reservoirs: Novel findings from hydrostatic pressure simulation experiments - Kehong Yu; Beibei Chai; Tianyu Zhuo; Qingfeng Tang; Xia Gao; Jiamin Wang; Lixin He; Xiaohui Lei; Bin Chen (Water Research, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Variation in Sunshine Duration and Related Aerosol Influences at Shangdianzi GAW Station, China: 1958–2021 - Weijun Quan; Zhiqiang Ma; Ziming Li; Xiaolan Li; Yingruo Li; Xiangao Xia; Huaigang Zhou; Hujia Zhao; Zhenfa Wang; Weiwei Pu; Fan Dong; Di He; et al. (Journal of Meteorological Research, 2023)

Graphene nano zinc oxide reduces the expression and release of antibiotic resistance-related genes and virulence factors in animal manure - Haibo Zhang; Weikun Guan; Jun Shu; Sen Yu; Yingmin Xiong; Gao Liu; Yuhong Zhong; Jia Chen; Zhigang Zhao; Ning He; Qingfeng Xing; Dongsheng Guo; et al. (Science of The Total Environment, 2023)

Evaluating the impact of co-administered drug and disease on ripretinib exposure: A physiologically-based pharmacokinetic modeling approach - Chunyang Pan; Yifan Cheng; Qingfeng He; Min Li; Fengjiao Bu; Xiao Zhu; Xiaoyu Li; Xiaoqiang Xiang (Chemico-Biological Interactions, 2023)

In-situ activities of anaerobic bacteria and methanogenic archaea in shallow lakes over the Anthropocene: A case study of Lake Wuliangsu - Yuxin He; Qingfeng Zhao; Dayang Sun; Huanye Wang (Chemical Geology, 2023)

Geochemistry of rare earth elements and yttrium in Late Permian coals from the Zhongliangshan coalfield, southwestern China - Qingfeng Lu; Shenjun Qin; Hongyang Bai; Wenfeng Wang; De’e Qi; Xin He; Bofei Zhang (Frontiers of Earth Science, 2023)

Ni-Mn spinel aerogel catalysts with adsorption induced superior activity for Low-Temperature toluene oxidation - Jiaqin He; Xunxun Li; Yaru Wang; Jun Xiao; Yunchong Liu; Hua Li; Najun Li; Qingfeng Xu; Jinghui He; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2023)

Simultaneous promotion of mechanical and electrical properties of hot-pressing halloysite-based mullite ceramics through carbon incorporation - He Zhang; Liangcao Yin; Qingfeng Liu; Yazhong Chen; Shi Jin; Kesong Xiao; Huanyu Zhu; Xianlong Zhang; Xueping Wu (Applied Clay Science, 2023)

Low quantity of Pt loaded onto CeCoOx nanoboxes: Surface–rich reactive oxygen species for catalytic oxidation of toluene - Yunchong Liu; Xunxun Li; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jinghui He; Jianmei Lu (Journal of Hazardous Materials, 2023)

Sulfonate-modified calixarene-based porous organic polymers for electrostatic enhancement and efficient rapid removal of cationic dyes in water - Lechen Tian; Shiyuan Zhou; Jiaojiao Zhao; Qingfeng Xu; Najun Li; Dongyun Chen; Hua Li; Jinghui He; Jianmei Lu (Journal of Hazardous Materials, 2023)

Association between environmental phenols and all-cause and cancer mortality - Jing He; Qingfeng Xue; Xin Hua; Quanqing Li; Ziwei Chen; Cindy Zhu; Wenyu Shi (Environmental Science and Pollution Research, 2022)

The combined effect of titanium dioxide nanoparticles and cypermethrin on male reproductive toxicity in rats - Yuxin Li; Mingqing Zhong; Xianzhi He; Ruoyu Zhang; Yu Fu; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Environmental Science and Pollution Research, 2022)

Can digital finance promote corporate green innovation? - Jiamin Liu; Yalin Jiang; Shengdao Gan; Ling He; Qingfeng Zhang (Environmental Science and Pollution Research, 2022)

Partitioning behaviors of zinc in eight coal-fired power plants with different fueled coals and air pollution control devices - Xian Zhou; Xinbin Feng; Xiangyang Bi; Xinyu Li; Qingfeng Wang; Shan Li; Tianrong He; Zhonggen Li (Environmental Science and Pollution Research, 2021)

Alpha 1-antichymotrypsin may be a biomarker for the progression of amnestic mild cognitive impairment - Shunjie Liu; Junhao Pan; Ke Tang; Qingfeng Lei; Lu He; Xiaodong Cai; Zhong Li (Acta Neurologica Belgica, 2021)

Serological characteristics of COVID-19 patients - Mi Zhou; Jing Zhong; Lei Bi; Pengcheng Shang; Yan Xing; Bo Wang; Jianlan He; Ying Xu; Tao Luo; Maohua Ma; Qingfeng Li (Infectious Diseases, 2020)

Assessing impacts of climate change on habitat suitability of Coregonus ussuriensis and other coldwater fishes in northern China - Baoxiu Xing; He Chen; Qingfeng Chen; Yan Zhang; Zifang Liu; Zhao Yang (Environmental Science and Pollution Research, 2019)

Extraction Optimization and Characterization of Gelatin from Half-Smooth Tongue Sole ( Cynoglossus semilaevis Gunther) Skin - Yanjie Li; Chunming Tang; Qingfeng He; Xiaodan Li; Ailin Zhang (Journal of Aquatic Food Product Technology, 2019)

A new azaphilone from the entomopathogenic fungus Hypocrella sp. - Qingfeng Guo; Lili Dong; Xiangyun Zang; Zijian Gu; Xiaoyun He; Lindan Yao; Liping Cao; Junzhi Qiu; Xiong Guan (Natural Product Research, 2015)